Classification, genesis and characterization of spatial variability of soils derived from sedimentary rocks in Malaysia / Wong Mum Keng - Wong, Mum Keng (2019)
In Malaysia, soils derived from sedimentary rocks are extensively used for agricultural purposes with oil palm and rubber being the main use. This study was carried out to determine the variability of physicochemical properties and classification of soils developed on sedimentary rocks under different ecosystems over natural forest and agriculture land. Therefore, three related studies were set up for this purposes. This first study focused on describing, sampling and analyzing physicochemical properties of twenty-five representative soil profiles taken from six study sites with different rainfall regimes spread across Malaysia. The soils are classified into 19 subgroups with qualifiers according to the World Reference Base for Soil Resources, 13 subgroups according to the USDA Soil Taxonomy and 15 subgroups according to the Malaysian Soil Taxonomy. Soil macronutrients contents were generally higher in the forest ecosystems followed by rubber plantations and finally oil palm plantations. From the principal component analysis(PCA) projection, it was found that soil physicochemical properties and microhabitats form an associative relationship. For the different agricultural and natural sites that have distinctive weathering condition and soil utilization, a comprehensive strategy is needed for maximizing the release of inorganic nutrients from sedimentary rocks and retaining them in bioavailable forms in the soil for sustainable crop production and ecosystem services. The second study focused on characterizing soil physiochemical properties of six soil profiles located along an altitudinal gradient (900 – 1900 m a.s.l.) developed from sedimentary parent rocks on Mount Alab, Sabah. The soils of the highest topographical position consisted of soils with a thin organic surface horizon, while the soils of the lower parts of the topographical positions were Inceptisols and finally Ultisols. All six pedons showed remarkable variability in morphological, physiochemical and clay mineralogical properties depending on the variations of the parent material. Field observations, soil physiochemical as well as clay mineralogical results of this study provide useful baseline information for soil conservation purposes in the tropics. The third study focus on quantifying the spatial variability of soils physicochemical properties in an oil palm plantation. Two study sites on oil palm plantation were chosen by soils that derived from similar parent material (sedimentary rock) with different soil series (Bungor and Chat series) characteristics. Soil samples were collected for surface (0-15 cm) and subsurface horizons (15-30 cm) from three management zones including weeded circle, harvest path and frond heap using a grid system. Leaf samples of front 17 were sampled from selected palms. Soil nutrients were higher at weeded circle and front heap as compare with harvest path in Bungor study site. On the contrary, different management zones of Chat study site shown less prominent differences in soil nutrients. This suggested that soil physical properties mainly soil texture plays an important role in determining spatial distribution pattern of soil nutrients. The outcomes from the spatial study can help to improve estate management strategies such as adapting a fertilizer application program that is more sitespecific based on the nutrient requirement to replenish the nutrient depleted from the soils.